Pepsinogen-II 100 bp ins/del gene polymorphism and its elevated circulating levels are associated with gastric cancer, particularly with Helicobacter pylori infection and intestinal metaplasia - Kumar, Sushil; Kumari, Niraj; Mittal, Rama D.; Ghoshal, Uday C. (Gastric cancer : official journal of the International Gastric Cancer Association and the Japanese Gastric Cancer Association, 2016)
Background Polymorphism in the gene of pepsinogen-II (PG-II) and its serum level are effective biomarkers for terminal differentiation of gastric mucosa into gastritis, intestinal metaplasia (IM), and gastric cancer (GC) in relationship to Helicobacter pylori infection. Methods Genotyping of the PG-II 100 bp insertion/deletion (ins/del) polymorphism was performed in patients with GC ( n = 192) and age- and gender-matched H. pylori -associated dyspepsia ( n = 180) and healthy subjects (HS, n = 240) by PCR. IgG anti- H. pylori (in all subjects) and serum PG-II levels were estimated in 145 patients each with GC and dyspepsia and in 65 healthy controls (HC) using ELISA (Biohit Oyj, Finland). Results Five alleles were amplified by PCR: allele 5 (510 bp), allele 4 (480 bp), allele 3 (450 bp), allele 2 (400 bp), and allele 1 (shorter allele, 310 bp). Allele 1 carriage was infrequent, and serum PG-II level was higher among patients with GC than in HC [OR 0.43 (95 % CI, 0.29–0.85), p < 0.001 and mean ± SD; 17.53 ± 12.60 vs. 12.77 ± 7.53 µg/l, p = 0.005, respectively], particularly in the presence of H. pylori [OR 0.42 (0.25–0.71), p = 0.001 and 18.78 ± 12.63 vs. 13.97 ± 8.14, p = 0.034]. However, allele 1 carriage and PG-II levels were comparable among patients with GC and dyspepsia. Patients with IM also carried allele 1 infrequently and had higher levels of PG-II than those without [OR 0.5 (0.29–0.85), p = 0.011 and 20.07 ± 14.22 vs. 16.61 ± 12.08, p = 0.048]. Conclusions Carriage of the shorter allele of the PG-II 100 bp ins/del polymorphism and elevated levels of PG-II are associated with GC, particularly with H. pylori infection and IM.